2007
DOI: 10.1111/j.1365-2648.2007.04250.x
|View full text |Cite
|
Sign up to set email alerts
|

Caring for a relative with dementia: family caregiver burden

Abstract: Caregivers, especially women, need individualized, specific training in how to understand and manage the behaviour of relatives with dementia and how to cope with their own feelings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
315
4
28

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 431 publications
(380 citation statements)
references
References 102 publications
(234 reference statements)
33
315
4
28
Order By: Relevance
“…A recent study emphasizes that neuroticism is a predictor of negative emotion coping and not of the use of specific coping strategies (Chappell and Dujela, 2009). In turn, it was found that high burdened relatives use more emotional-focused coping strategies, while less burdened relatives used more problemsolving approaches to caregiving demands (Papastavrou et al, 2007). Importantly, caregivers who were identified as less responsive and less psychological available were shown to have a coping style that was correlated to shorter survival time in persons with dementia (McClendon et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study emphasizes that neuroticism is a predictor of negative emotion coping and not of the use of specific coping strategies (Chappell and Dujela, 2009). In turn, it was found that high burdened relatives use more emotional-focused coping strategies, while less burdened relatives used more problemsolving approaches to caregiving demands (Papastavrou et al, 2007). Importantly, caregivers who were identified as less responsive and less psychological available were shown to have a coping style that was correlated to shorter survival time in persons with dementia (McClendon et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This finding was not unexpected, as in most cultures women are perceived as nurturing, and so caregiving is often a socially imposed occupation. 9 Numerous sources of stress and caregiver burdens have been identified by research. These stressors range from having to perform daily self-care tasks, such as bathing and feeding, to coping with adverse problem behaviours, such as wandering off and becoming disorientated in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Tais mudanças os tornam percepção de estresse (estratégias de enfrentamento); e as consequências dos cuidados sobre o bem-estar geral do cuidador (PAPASTAVROU et al, 2007).…”
Section: Cotidiano Dos Cis E O Processo De Cuidar Do Outrounclassified
“…No presente estudo, o CI foi definido como o principal responsável pelo paciente, por prover os cuidados requeridos por ele e não possuir formação especializada para exercer a função de cuidador. Essa função muitas vezes implica não somente em cuidar do doente mas também em conciliar os cuidados à organização e gerenciamento das atividades e afazeres domésticas, exigindo que o CI reorganize a rotina de atividades diárias e seu cotidiano (PEDRO; MARCON, 2007). Tal aspecto mostra-se relevante, particularmente para a Terapia Ocupacional, que se caracteriza como uma área de conhecimento e uma prática de saúde que tem como objeto de conhecimento e intervenção os problemas do homem em sua vida cotidiana de atividades.…”
unclassified